Intimate partner violence among pregnant women in Uganda - Epuitai, Joshua; Udho, Samson; Auma, Anna Grace; Nabirye, Rose Chalo (African Journal of Midwifery and Women's Health, 2019)
Intimate partner violence may be more prevalent during pregnancy as women are more vulnerable. To determine the prevalence of intimate partner violence and associated factors among pregnant women at Soroti Regional Referral Hospital, Uganda. A cross-sectional study was conducted among 180 pregnant women. Data were collected using a pre-tested, semi-structured questionnaire. Intimate partner violence was measured using the revised Conflict Tactile Scale 2. The overall prevalence of intimate partner violence during pregnancy was 27.8%. Household average monthly income, experiences of intimate partner violence before pregnancy and marital conflicts were independently associated with intimate partner violence during pregnancy. Screening should be done during antenatal care among women with low household income, marital conflicts, and history of intimate partner violence before pregnancy to identify and manage cases of intimate partner violence. More research is needed to identify interventions for reduction of intimate partner violence during pregnancy.